Death in the individual Psalms of lament: an exegetical study with implications for theology and mission - Grantson, Emmanuel F. Y. (Lutheran School of Theology, 1991)
The thesis argues that certain aspects of death in the individual lament psalms when viewed in the light of socio-economic perspectives provide new insights into the Old Testament definition of death. These aspects are clarified in an exegetical study of selected psalms (Pss. 88; 7; 64; 13; 6; 30; 49) and elaborated through the examination of expressions such as 'wyb, sr, 'nsy dmym, mwt, dwmh, rs', p'ly 'wn. There is a good use of socio-anthropology dealing with personal causality, its relationship to the healing process, and Yahweh's link to the kinship and social order as a necessary ingredient for change in the social order as previously known. The research is located within the history of psalm interpretation, with emphasis on the works of Christoph Barth, Mitchell Dahood and Nicholas Tromp. The evidence that death may be conceived as a form of socio-economic oppression, and as a pattern of ideology is located within the milieu of sorcery, magic, witchcraft, and within the political context of the Israelite monarchy in the 8th and 7th centuries B.C.E. The dissertation begins by defining the problem, its parameters, and the methodological principles for the study. This is followed by a detailed critical exegetical analysis, and a discussion of the various aspects of death. The conclusion is reached that death was perceived in the psalms as a diminution of life and as a matter of degree; that death motifs are pervasive in the psalms; that interpreting the psalter with socio-anthropological data while using the biblical material as the controlling factor is tenable. The dissertation's implications are theological and missiological. Theologically, it opens up the way for a cross-cultural dialogue between the Hebrew scriptures and African theologians, and the possibilities for liberation hermeneutics. Missiologically, it provides the key for understanding the African's need to be Christian and African without losing essential parts of her cultural heritage.
paid
Keywords: Academic Dissertation; Academic theses; Africa; Bibel Psalmen; Bible. Psalms; Tod; psalm 13; psalm 30; psalm 49; psalm 6; psalm 64; psalm 7; psalm 88